Narciso, Adão ou Cristo americano: Egoísmo e altruísmo em Canção de Mim Mesmo em Walt Whitman - Oliveira Junior, Nelson Perez de (2012)
The goal of this dissertation is to analyze the composition of the several personalities and characters assumed by the Whitman’s poetic selves in the poem Song of Myself from the facsimile bilingual Brazilian edition with translation of Rodrigo Garcia Lopes. We also seek to verify how the articulation of these multifaced poet selves moved by selfishness and altruism produced the effect of an identification of the poet with the readers and the North American nation, the USA. For that it has been necessary to understand the influence of myths and of the founder fathers of colonization and independence of USA and the consequent invention of North American man. The cultural, economic, political, and social conditions and the technical revolution in the XIX century were fundamental and single for the setting of the myth of this American man in the nation’s imagery. The media industry revolution searched technical innovations in the language form and, economically, with smaller prices to communicate with this man. Whitman, being a journalist, was as sensible to all these single conditions as to this audience of readers. He configured his poetry to this audience. Whitman built his poetry based on the strength of images of himself and his time. The images of Deleuze-Guattari, noticeably from Rhizome and the Tree and the Desiring Machines were fundamental for our pragmatic and empirical approach of Whitmanian poetry. The prefaces of the facsimile edition and the postface of deathbed edition, translated by Bruno Gambarotto and some other poems of Whitman were used, beyond the texts that propitiated us to outline the images of Whitman in the building of his multiple poetic personality, of his iconographic image and of his book Leaves of Grass.